Secure lossless transmission of correlated sources over noisy broadcast channel using separate source-channel coding - Fei LANG; Bao-yun WANG; Zhi-xiang DENG (Tongxin xuebao)
The problem of secure transmission of correlated sources over broadcast channel was studied from the pers-pective of information-theoretic security.Each source is only for its intended receiver,but to be kept secret from the un-intended receiver.Sufficient condition was provided for secure transmission of correlated sources over broadcast channels from separate source-channel coding perspective.If the mutual information was chosen as common information,optimal compression and partial perfect secrecy were both achieved for two correlated sources.Sufficient and necessary condi-tions were provided for two special cases:a broadcast channel with degraded source sets and a more capable broadcast channel,and thus it could be seen that the separate source-channel code is optimal.